Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Sure, let me walk you through the steps to solve the expression [tex]\( (a + b) \cdot c - d \)[/tex] in a detailed manner.
### Step-by-Step Solution
1. Step 1: Calculate [tex]\(a + b\)[/tex]
First, add the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex].
[tex]\[ \text{sum\_ab} = a + b \][/tex]
2. Step 2: Multiply the Sum by [tex]\(c\)[/tex]
Next, take the result from Step 1 and multiply it by [tex]\(c\)[/tex].
[tex]\[ \text{product\_abc} = \text{sum\_ab} \cdot c = (a + b) \cdot c \][/tex]
3. Step 3: Subtract [tex]\(d\)[/tex]
Finally, subtract [tex]\(d\)[/tex] from the result obtained in Step 2.
[tex]\[ \text{result} = \text{product\_abc} - d \][/tex]
4. Step 4: Summarize the final expression
Combining all the steps, the final result will be:
[tex]\[ \text{result} = (a + b) \cdot c - d \][/tex]
Let's use some example values to demonstrate:
- Suppose [tex]\(a = 2\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = 4\)[/tex]
- [tex]\(d = 5\)[/tex]
Calculations:
1. Calculate [tex]\(a + b\)[/tex]:
[tex]\[ a + b = 2 + 3 = 5 \][/tex]
2. Multiply by [tex]\(c\)[/tex]:
[tex]\[ (a + b) \cdot c = 5 \cdot 4 = 20 \][/tex]
3. Subtract [tex]\(d\)[/tex]:
[tex]\[ 20 - 5 = 15 \][/tex]
So, the final result with these values would be:
[tex]\[ 15 \][/tex]
### General Formula
In general terms, if you know the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], [tex]\(c\)[/tex], and [tex]\(d\)[/tex], you can always use the steps outlined above to find the result of the expression [tex]\( (a + b) \cdot c - d \)[/tex].
### Step-by-Step Solution
1. Step 1: Calculate [tex]\(a + b\)[/tex]
First, add the values of [tex]\(a\)[/tex] and [tex]\(b\)[/tex].
[tex]\[ \text{sum\_ab} = a + b \][/tex]
2. Step 2: Multiply the Sum by [tex]\(c\)[/tex]
Next, take the result from Step 1 and multiply it by [tex]\(c\)[/tex].
[tex]\[ \text{product\_abc} = \text{sum\_ab} \cdot c = (a + b) \cdot c \][/tex]
3. Step 3: Subtract [tex]\(d\)[/tex]
Finally, subtract [tex]\(d\)[/tex] from the result obtained in Step 2.
[tex]\[ \text{result} = \text{product\_abc} - d \][/tex]
4. Step 4: Summarize the final expression
Combining all the steps, the final result will be:
[tex]\[ \text{result} = (a + b) \cdot c - d \][/tex]
Let's use some example values to demonstrate:
- Suppose [tex]\(a = 2\)[/tex]
- [tex]\(b = 3\)[/tex]
- [tex]\(c = 4\)[/tex]
- [tex]\(d = 5\)[/tex]
Calculations:
1. Calculate [tex]\(a + b\)[/tex]:
[tex]\[ a + b = 2 + 3 = 5 \][/tex]
2. Multiply by [tex]\(c\)[/tex]:
[tex]\[ (a + b) \cdot c = 5 \cdot 4 = 20 \][/tex]
3. Subtract [tex]\(d\)[/tex]:
[tex]\[ 20 - 5 = 15 \][/tex]
So, the final result with these values would be:
[tex]\[ 15 \][/tex]
### General Formula
In general terms, if you know the values of [tex]\(a\)[/tex], [tex]\(b\)[/tex], [tex]\(c\)[/tex], and [tex]\(d\)[/tex], you can always use the steps outlined above to find the result of the expression [tex]\( (a + b) \cdot c - d \)[/tex].
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.